2021
DOI: 10.3892/ijmm.2021.4952
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑101 inhibits renal tubular epithelial‑to‑mesenchymal transition by targeting TGF‑β1 type I receptor

Abstract: MicroRNAs (miRNAs/miRs) are key regulators of renal interstitial fibrosis (RIF). The present study was designed to identify miRNAs associated with the development of RIF, and to explore the ability of these identified miRNAs to modulate the renal tubular epithelial-to-mesenchymal transition (EMT) process. To this end, miRNAs that were differentially expressed between normal and fibrotic kidneys in a rat model of mercury chloride (Hgcl 2 )-induced RIF were detected via an array-based approach. Bioinformatics an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…MicroRNAs (miRNAs/miRs) are a novel class of non-coding small ribonucleic acids, which can regulate gene expression by suppression of mRNA translation or degradation of mRNAs ( 11 , 12 ). Moreover, miRNAs participate in cellular process, including the growth of renal tubular epithelial cells ( 13 , 14 ). Meanwhile, miRNAs have been reported to be associated with AKI progression ( 15 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs/miRs) are a novel class of non-coding small ribonucleic acids, which can regulate gene expression by suppression of mRNA translation or degradation of mRNAs ( 11 , 12 ). Moreover, miRNAs participate in cellular process, including the growth of renal tubular epithelial cells ( 13 , 14 ). Meanwhile, miRNAs have been reported to be associated with AKI progression ( 15 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has shown that up-regulation of miR-101 inhibits acute kidney injury and chronic kidney disease transition by regulating epithelial–mesenchymal transition [ 21 ]. Another work demonstrated that miR-101-3p is a regulator of renal interstitial fibrosis inhibiting TGF-β1-induced tubular EMT by targeting TβR-I [ 22 ]. Zhao et al revealed that miR-101-3p negatively regulates inflammation in SLE via MAPK1 targeting and blocking the NF-κB pathway [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…miR-101-3p has been reported on over the last 3 years. Wang et al found miR-101 reverse TGFβ1 induced epithelial-to-mesenchymal transition (EMT) in HK 2 cells with less fibrosis [ 33 ]. Zhao et al also revealed that miR-101 inhibits AKI-to-CKD transition by regulating EMT [ 34 ].…”
Section: Discussionmentioning
confidence: 99%